Pengaruh Struktur Modal, Volatilitas Penjualan dan Tingkat Hutang Terhadap Persistensi Laba Pada Perusahaan Infrastruktur Yang Terdaftar Di BEI Periode 2018-2021 - Saragi, Dame Ria Rananta; Sihombing, Halomoan; Manurung, Juliana Novelentina (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
The aim of this research is to find out how capital structure, sales volatility and debt levels affect profit persistence. Infrastructure companies listed on the Indonesia Stock Exchange from 2018 to 2021 are the subject of this research. In this research, the purposive sampling method was used to select 16 companies with 4 periods, or the equivalent of 64 samples used. This research uses multiple linear regression data analysis. Based on the results of hypothesis testing, it can be concluded that, while company size influences earnings persistence, debt levels partially influence earnings persistence. In addition, sales volatility shows a negative correlation, which means that sales volatility does not affect profit persistence.